2021
DOI: 10.1155/2021/1075513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psychological Intervention Combined with Dietary Guidance on Quality of Life and Long-Term Efficacy of Bushen Quyu Decoction in Treatment of Patients with Advanced Ovarian Cancer

Abstract: Objective. To study the effects of psychological intervention combined with dietary guidance on the quality of life and long-term efficacy of Bushen Quyu Decoction in the treatment of patients with advanced ovarian cancer. Methods. 220 patients with advanced (stages III to IV) ovarian cancer in our hospital from May 2015 to October 2018 were selected and randomly divided into a control group and an observation group, with 110 cases in each group. The patients in the control group received basic nursing care an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…In recent years, with the enhancement of health consciousness, people have paid more and more attention to dietary intervention for cancer prevention and management, and some natural products with wide sources and low or no toxicity have shown promising efects in this regard [18,19]. LR (also called black goji berry) is a wild prickly shrub, which is mainly planted in northwestern China such as Ningxia, Qinghai, and Xinjiang due to its unique drought-resistant and salt-resistant characteristics [20].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the enhancement of health consciousness, people have paid more and more attention to dietary intervention for cancer prevention and management, and some natural products with wide sources and low or no toxicity have shown promising efects in this regard [18,19]. LR (also called black goji berry) is a wild prickly shrub, which is mainly planted in northwestern China such as Ningxia, Qinghai, and Xinjiang due to its unique drought-resistant and salt-resistant characteristics [20].…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 11 ] Although a large number of patients with OC benefit from surgery, it is accompanied by a variety of complications, such as anxiety and depression. [ 12 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Although a large number of patients with OC benefit from surgery, is accompanied by a variety of complications, such as anxiety and depression. [12][13][14] Previous studies have reported that HQNC has potential to reduce anxiety and depression in patients with cancer during PPP. [15][16][17][18][19] Furthermore, a variety of clinical trials have focused on the management of psychological disorders in patients with OC during PPP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations